Dynamic and static viscosity and elasticity moduli of binary mixtures of polyhydroxyalcohols - WACIŃSKI, Marek; ZORĘBSKI, Edward; BEBEK, Krzysztof (Archives of Acoustics, 1984)
This paper presents the results of measurements of viscosity and mechanical shear impedance, for frequencies of 0.5, 500 and 600 MHz, of liquid mixtures of glycerol-2-methylpentanedio1-2.4 and glycerol-butanedio1-1.3. The components of mechanical shear impedance, dynamic viscosities, relaxation times and limiting shear moduli were calculated. This permitted the determination of the reaction of the liquids under study to shear deformation over a wide frequency range, including viscous, viscoelastic and pure elastic reactions.